Zinc supplementation of parenteral nutrition in newborn infants - Taylor, Andrea J (Cochrane Database Syst Rev, 2017)
This is a protocol for a Cochrane Review (Intervention). The objectives are as follows: The primary objectives are to determine the effectiveness and safety of parenteral zinc supplementation with regards to morbidity and mortality in parenterally fed term and preterm infants. Secondary objectives are to determine: 1. Which infants (within predefined subgroups: gestational age ‐ term, preterm, very preterm, extremely preterm; birthweight ‐ low birth weight, very low birth weight, extremely low birthweight; and, infants at greater risk of zinc deficiency due to specific illnesses) would benefit most from zinc supplementation; 2. The optimal dose of parenteral zinc supplementation: lower (< 450 μg/kg per day for preterm infants and < 250 μg/kg for infants less than 3 months) versus higher dose (≥ 450 μg/kg per day for preterm infants and ≥ 250 μg/kg per day for infants less than 3 months) zinc supplementation; and 3. The optimal timing of parenteral zinc supplementation: early (commenced at < 2 weeks of age) versus late (commenced at ≥ two weeks of age).